A New Vocational Education Marketing Mix in Indonesia - Kurniawan, Asep; Jamaluddin (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
Based on the experience of vocational high school students, this article aims to present a new marketing mix. Opinions and perspectives on vocational high school marketing efforts in Indonesia. In their attempt to attract students to vocational education, the vocational educational market becomes increasingly aggressive. Over the years, conventional marketing tools grouped into four P (product, price, location, promotion), and 5 P (adding people), and 7P (adding processes and facilities physically). This tool may be short on the market today. This method uses a quantitative survey of vocational school students in the city of Cirebon. Finding: The factor data analyzed showed seven very different key factors in marketing these vocational high school activities. Some of these factors include traditional integration elements of marketing such as people, promotions, and prices. Nevertheless, there are four different components: program, excellence, prospectus, and premium. This study only looked at small and medium-sized students in the city of Cirebon. However, the results suggest that, as initially assumed, the marketing of this mixed traditional service may not benefit the vocational secondary education sector. With this 7P, the development of marketing strategies can be done better.